Adsorption of direct red 79 in wastewater on Fe2Fe1-xMnxO4 (x = 0 - 1) nanoparticles prepared by co-precipitation method - Pham Hoai, Linh; Nguyen Quoc, Dung; Nguyen Van, Khien (Vietnam Journal of Science and Technology, 2023)
Magnetic spinel ferrite nanoparticles Fe2Fe1-xMnxO4 were synthesized by a simple co-precipitation method. The morphology and structures of the synthesized samples were characterized by X-ray diffraction (XRD), field-emission scanning electron microscope (FE-SEM), Raman spectroscopy, and infrared spectroscopy (FTIR). The magnetic properties of the materials were studied using VMS measurement. The results showed that the spinel ferrite nanoparticles formed a single phase of packed face-centered cubic spinel structure. When replacing Mn2+ ions with Fe2+, the crystal structure shifted from the Fe3O4 crystal structure to the MnFe2O4 crystal structure assigned with an increased lattice constant from 6.30 nm to 26.33 nm. Raman and FTIR spectrum analysis showed that when replacing Mn2+ ions with Fe2+, the Mn-O and Fe-O bonds changed significantly. Specifically, the intensity of the Raman spectrum's reflection and the FTIR spectrum's absorption decreased gradually. All the samples exhibited uniform spherical shapes, and particle size varied from 9.8 nm to 30 nm, depending strongly on the substituted concentration. The magnetization curves confirm the soft ferromagnetic behavior with close superparamagnetic properties of Fe2Fe1-xMnxO4 nanoparticles. The material used to study the adsorption of Direct Red 79 (DR79) in water has good adsorption capacity. The adsorption process obeys pseudo-second-order kinetics and also shows compliance with Langmuir, Freundlich and Temkin isotherms.